PERANCANGAN MEDIA EDUKASI INTERAKTIF ENSIKLOPEDIA ASTRONOMI UNTUK ANAK-ANAK - ASADULLAH ABDUL QOHAR, Dr. M. Nasrul Kamal, M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The purpose of designing interactive educational media encyclopedia of astronomy is as an effort to increase  interest in reading in children as the target audience. There are a lot of books about astronomy, but the  interest in reading in Indonesia is very low, especially in the age groups of children at this time more opiate use gadgets such as smartphones. Research method that I use is the qualitative method. The design of this  interactive educational media using Visual Communication Design theory, interactive media, learning, logos,  illustration, typography, layout, and color. In the design of interactive educational media, the author uses the  method 5W1H (what, where, who, why, when, how). This design is also supported by several media such as t-shirts, posters, x-banners, stickers, key chains, pins, bookmark, and instagram.Keyword : Education Media Design Interactive, Encyclopedia, Astronomy